An assessment of the role of government in youth socio economic empowerment: a case of Kurera/Ukondla youth fund in Hwange - Nkomo, Trish (Midlands State University, 2017)
This study concentrates on the role of government in guaranteeing youth socio economic empowerment, investigating the project Kurera/Ukondla youth fund. The plague of youth unemployment has been recognized as one of the major encounters facing youngsters around the globe, with developing opinion slanting towards microloans as an answer, on the other hand access to capital is a huge problem confronting youth in Zimbabwe in the formation and growth of small business. Access to loans has revealed to be significant when it comes to youth socio economic empowerment. This study enhances the examination on Kurera/Ukondla youth fund on the grounds that it considers the effect from a youth monetary development point of view. It likewise highlights the criticism from the dispensing bank CABS, Ministry of Youth Development, Indigenisation and Empowerment officers and youth members by emulating participatory system assessment systems. The Kurera/Ukondla youth trust was an intervention by the government of Zimbabwe in attempting to manage youth unemployment in the country. The research was largely qualitative in nature and it demonstrated that the micro finance project had a trifling impact on various young people in Hwange, in spite of the fact that uptake of the trust was high, this did not mean profundity. However positive impacts of the youth fund project extend on youth financial benefit in the fleeting were noted. Some of the recommendations that were put in order to address the shortfall of Kurera/Ukondla youth fund and ensure effectiveness of the project was that it should be decentralised so that it could reach the rural youths and there should be effective awareness campaigns.